Synonymous variants in the ATP6AP2 gene may lead to developmental and epileptic encephalopathy - Liang, Yan; Wan, Lin; Yan, Huimin; Liu, Xinting; Zhang, Jing; Zhu, Gang; Yang, Guang (Frontiers in Neurology, 2024)
Objective To the literature, variants in the ATP6AP2 gene may cause abnormal nervous system development and associated neurological symptoms. Methods We report a patient with developmental and epileptic encephalopathy (DEE) carrying an ATP6AP2 c.858G > A (p.Ala286=) synonymous variant. In addition, an overview of reported patients with the same variant were collected and summarized to compare our findings. Results The patient started experiencing tonic seizures at 3.5 months of age, and magnetic resonance imaging (MRI) indicated impaired brain white matter development and reduced left hippocampal volume. Furthermore, electroencephalography showed multifocal interictal epileptiform discharges. Treatment with various anti-seizure medications yielded unsatisfactory results, and the disorder eventually developed into epileptic spasms. An in vitro splicing assay for the ATP6AP2 gene mRNA revealed that the variant caused a deletion in exon 8 and a corresponding protein truncation. A review of previously reported ATP6AP2-related DEE patients found that synonymous variants in the ATP6AP2 gene can cause early DEE onset, progressive changes in early-life MRI, and exon skipping in all ATP6AP2-related DEE patients. Significance We found that synonymous variants in ATP6AP2 may have significant pathogenicity and are highly correlated with DEE. Due to increased isoform production, ATP6AP2 synonymous variants may cause nervous system developmental disorders by competitively reducing the generation of full-length transcripts, resulting in defects in ATP6AP2-related physiological processes.